Optimal Afforestation Contracts with Asymmetric information on Private Environmental Benefits - Signe Anthon; Bo Jellesmark Thorsen (Fondazione Eni Enrico Mattei (FEEM), 2004)
We investigate the problem of subsidising afforestation when private information exists with respect to the level of private utility derived from the project. We develop a simple model that allows for an intelligent design of contracts when information is asymmetric. The model involves the Principal and two groups of agents (landowners): a green' group deriving high private utility from the projects and a conventional' group deriving lower utility. Afforestation projects may be produced in different environmental quality, and we distinguish between two cases, a high quality and a low quality project. We find that the optimal set of contracts under asymmetric information involves two different contracts. One in which green landowners are somewhat overcompensated for projects of high quality, and one where conventional landowners are offered contracts including lower quality projects, compared to the symmetric case, but with compensation equal to his indifference payment. It is the ability to reduce quality requirements along with subsidies offered that allows for revelation of the private information. Finally, we discus how the results obtained may be used in the implementation of incentive schemes.
Keywords: D82; H23; Q23; 330; Principal-agent theory; Incentive schemes; Revelation principle; Environmental economics; Aufforstung; Subvention; Asymmetrische Information; Prinzipal-Agent-Theorie; Leistungsanreiz; Leistungsanreiz; Vertrag